Interpersonal and Ideational Metaphors in the Writing of Thesis Texts of Undergraduate Students of English Study Program: A Systemic Functional Linguistic Approach - Magdalena Ngongo; Naniana Benu (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2020)
This study describes how interpersonal and ideational metaphors were realised in th writing of theses texts written by undergraduate students of English study program. This study is a documentary analysis of descriptive method. Data in the form of corpus data were randomly taken from 15 theses among 70 theses in population. Data were analyzed by focusing on the semantic functions covering interpersonal and ideational metaphors. The results showed that interpersonal metaphor was realised in mood system and modality. Mood system was realised mostly in declarative clauses than interrogative and imperative ones. This fact was caused by the channel of text, written text. Modality was least used in the texts. Ideational metaphor was sin transitivity system in which material process was mostly applied than mental, behaviour, existential, relational and verbal processes. Nominalisation was selected as the mostly used property of linguistic feature in writing theses. Ideational metaphor was more used than interpersonal metaphor. This fact happens due to the text channel, written text. Therefore, it is suggested that lecturers in their teaching should consider their teaching by including metaphorical meaning, especially ideational and interpersonal metaphors. Besides, it is suggested to conduct research by comparing languages, national or international languages such as between Indonesian and English or else.